Evolutionary ecology of aging: time to reconcile field and laboratory research - Reichard, Martin (Ecology and evolution, 2016)
Aging is an increase in mortality risk with age due to a decline in vital functions. Research on aging has entered an exciting phase. Advances in biogerontology have demonstrated that proximate mechanisms of aging and interventions to modify lifespan are shared among species. In nature, aging patterns have proven more diverse than previously assumed. The paradigm that extrinsic mortality ultimately determines evolution of aging rates has been questioned and there appears to be a mismatch between intra- and inter-specific patterns. The major challenges emerging in evolutionary ecology of aging are a lack of understanding of the complexity in functional senescence under natural conditions and unavailability of estimates of aging rates for matched populations exposed to natural and laboratory conditions. I argue that we need to reconcile laboratory and field-based approaches to better understand (1) how aging rates (baseline mortality and the rate of increase in mortality with age) vary across populations within a species, (2) how genetic and environmental variation interact to modulate individual expression of aging rates, and (3) how much intraspecific variation in lifespan is attributable to an intrinsic (i.e., nonenvironmental) component. I suggest integration of laboratory and field assays using multiple matched populations of the same species, along with measures of functional declines.
Keywords: senescence; intraspecific aging rate; gene‐by‐environment interaction; intrapopulation variability; Condition‐dependence; evolution of aging; mortality